Assessments of Acoustic Environments by Emotions – The Application of Emotion Theory in Soundscape - Fiebig, André; Jordan, Pamela; Moshona, Cleopatra Christina (Frontiers in Psychology, 2020)
Human beings respond to their immediate environments in a variety of ways, with emotion playing a cardinal role. In evolutionary theories, emotions are thought to prepare an organism for action. The interplay of acoustic environments, emotions, and evolutionary needs are currently subject to discussion in soundscape research. Universal definitions of emotion and its nature are currently missing, but there seems to be a fundamental consensus that emotions are internal, evanescent, mostly conscious, relational, manifest in different forms, and serve a purpose. Research in this area is expanding, particularly in regards to the context-related, affective, and emotional processing of environmental stimuli. A number of studies present ways to determine the nature of emotions elicited by a soundscape and to measure these reliably. Yet the crucial question—which basic and complex emotions are triggered and how they relate to affective appraisal—has still not been conclusively answered. To help frame research on this topic, an overview of the theoretical background is presented that applies emotion theory to soundscape. Two latent fundamental dimensions are often found at the center of theoretical concepts of emotion: valence and arousal. These established universal dimensions can also be applied in the context of emotions that are elicited by soundscapes. Another, and perhaps more familiar, parallel is found between emotion and music. However, acoustic environments are more subtle than musical arrangements, rarely applying the compositional and artistic considerations frequently used in music. That said, the measurement of emotion in the context of soundscape studies is only of additional value if some fundamental inquiries are sufficiently answered: To what extent does the reporting act itself alter emotional responses? Are all important affective qualities consciously accessible and directly measurable by self-reports? How can emotion related to the environment be separated from affective predisposition? By means of a conceptual analysis of relevant soundscape publications, the consensus and conflicts on these fundamental questions in the light of soundscape theory are highlighted and needed research actions are framed. The overview closes with a proposed modification to an existing, standardized framework to include the meaning of emotion in the design of soundscapes.